2018
DOI: 10.1055/s-0038-1667330
|View full text |Cite
|
Sign up to set email alerts
|

Glans Ischemia after Circumcision in a 16-Year-Old Boy: Full Recovery after Angiography with Local Spasmolysis, Systemic Vasodilatation, and Anticoagulation

Abstract: Circumcision is one of the most frequent procedures performed by pediatric surgeons. A dorsal penile nerve block (DPNB) is commonly used for perioperative analgesia. We report the case of a 16-year-old boy with ischemia of the glans who presented on the first postoperative day after circumcision under DPNB (0.25% bupivacaine) at an outside hospital. The patient underwent immediate angiography under sedation. An intra-arterial spasmolysis was performed with alprostadil and nitroglycerine and a sufficient perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Notably, in a similar case, Efe et al [ 5 ] reported an elevated D-dimer level, with restoration to normal level after five days of enoxaparin treatment, suggesting a penile vascular thrombosis even though CDI showed normal penile and glandular blood flow. Conversely, both Karaguzel et al [ 4 ] and Gnatzy et al [ 6 ] reported their experiences, describing two cases of acute GI after circumcision with a normal level of D-dimer and good penile blood flow at CDI. Regarding our cases, the first one showed normal blood flow at CDI but D-dimer value was not checked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in a similar case, Efe et al [ 5 ] reported an elevated D-dimer level, with restoration to normal level after five days of enoxaparin treatment, suggesting a penile vascular thrombosis even though CDI showed normal penile and glandular blood flow. Conversely, both Karaguzel et al [ 4 ] and Gnatzy et al [ 6 ] reported their experiences, describing two cases of acute GI after circumcision with a normal level of D-dimer and good penile blood flow at CDI. Regarding our cases, the first one showed normal blood flow at CDI but D-dimer value was not checked.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Aminsharifi et al [ 11 ] reported the use of topical testosterone, which has been shown to improve the vascular density of foreskin in vitro , in two cases of delayed GI after circumcision, which resulted in complete healing after one month. Selective angiography with intra-arterial injection of a vasodilator agent has been reported by Gnatzy et al [ 6 ] in association with oral sildenafil and infusion of L-arginine hydrochloride and unfractionated heparin. Lastly, as previously reported, anticoagulant therapy using enoxaparin has been effective in case of GI after circumcision[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we strongly recommend the use of preoperative imaging studies, intraoperative pictures/videos, or images of histopathologic examinations. 8,[17][18][19] With smartphones readily available, photo and video documentation has been further facilitated. 20,21 Obtain written permission from the patient (if appropriate), parents, or caregiver to use medical information and images.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Many journals (e.g., European Journal of Pediatric Surgery Reports ) do not use the standard subheadings (i.e., Introduction, Methods, Results, and Discussion referred to as IMRaD) in the abstract. 8 9 However, other journals encourage IMRaD even in the abstract. Thus, consult the “Instructions for Authors” of the target journal before you write the abstract.…”
Section: Introductionmentioning
confidence: 99%
“…The etiopathogenic mechanisms underlying this lesion are unknown, although it has been postulated that it may be related to preoperative anesthetic blockade (both in formulations with and without epinephrine), to the use of compressive penile bandages, and to the inadvertent damage of vascular structures during the procedure [1]. It has also been postulated that it may be in relation with a spasm of the dorsal artery of the penis, although the only documented case in which supraselective angiography was performed at diagnosis did not document vasospasm [2]. Briones/Bronte Anaut/Bardají Pascual…”
Section: Introductionmentioning
confidence: 99%